Activated bio-adhesives by natural sunlight - Syed Ikhwan Syed Ismail Alsagoff (Nanyang Technological University, 2020)
Bio-adhesives have gained an increasing popularity amongst researches in developing new biomaterials and therapies in the present era. Although bio-adhesives are known to allow less complications in surgeries, more research is still in progress to expand the use of bio-adhesives in other areas of the medical industry. The existence of various field medicine in the markets provides great competition in achieving the ideal on-demand, fast and instant wound treatment. However, some field medicine has specific needs in order for it to perform well, such as, the requirement of high intensity for the total curing of bio-adhesive. Although there are various field medicine available, there are some research gap in the study of field medicine. There are inconclusive report regarding the use of carbene bio-adhesives, which uses low light intensity for curing. There are also inconclusive prove that bio-adhesives can be used in deep wounds. This report will also be covering the various methods of curing carbene bio-adhesive and how it provides dangerous side-effects that would be harmful to the patients. The report will prove that an alternative method could potentially be a convenient way in wound treatment due to its low intensity and less side-effects. The data obtained in this report has allowed for more opportunities in exploring the activation of bio-adhesion. With most activation methods having severe side effects, exploration of methods of activation should be done. In this report, sunlight curing method was used and it is considered to be close to ideal due to its cheap and reliable method. Currently, there is no ideal activation methods as of yet and this report aims to provide broad discovery in improving existing methods.